1997
DOI: 10.1007/s001340050489
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ventilation in ventral decubitus position on respiratory mechanics in adult respiratory distress syndrome

Abstract: We observed an increase in oxygenation and Crs when the patients were turned from the supine to the prone position with the upper thorax and pelvis supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0
6

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 36 publications
(41 reference statements)
8
42
0
6
Order By: Relevance
“…Assuming that overall compliance of the diaphragmatic wall remains unchanged in the prone position, since the intra-abdominal pressure did not change, it could be supposed that the decrease in thoracoabdominal compliance arises through a greater stiffness of the posterior, compared to the anterior, wall of the thorax when free to move. Other authors have shown an improvement in respiratory system compliance in the prone position, but their data mainly refer to patients with "secondary" ARDS (nonpulmonary insult) [23][24][25]. Interestingly, respiratory system compliance is improved when patients are returned to the supine position [22].…”
Section: Effects On Respiratory Mechanicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Assuming that overall compliance of the diaphragmatic wall remains unchanged in the prone position, since the intra-abdominal pressure did not change, it could be supposed that the decrease in thoracoabdominal compliance arises through a greater stiffness of the posterior, compared to the anterior, wall of the thorax when free to move. Other authors have shown an improvement in respiratory system compliance in the prone position, but their data mainly refer to patients with "secondary" ARDS (nonpulmonary insult) [23][24][25]. Interestingly, respiratory system compliance is improved when patients are returned to the supine position [22].…”
Section: Effects On Respiratory Mechanicsmentioning
confidence: 99%
“…Only a minority (7%) investigated the effects between 2-4 h [27,61,62]. The majority of the studies investigated patients with a predominance (w80% of the studies) of primary ARDS [22, 27, 39-41, 43, 57] while a minority investigated patients with a predominance of secondary ARDS (11%) [24,56,62,63]. Approximately 40% investigated a group of patients with equally distributed primary and secondary ARDS (between 20-80%) [4,5,18,23,26,28,42,50,60,61].…”
Section: An Overview Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Decreased levels of total proteins in BAL accompained this alleviating effect on lung injury. Since West's accurate descriptions of the physiology of respiration and the ventilation/perfusion zones 12 , position change has been advocated to promote redistribution of gas, recruit alveoli, and redistribute pulmonary blood flow 13 .…”
Section: Discussionmentioning
confidence: 99%
“…São poucos os paraefeitos relacionados à mudança de decúbito; mais comumente, é visto o edema subcutâneo posicional, que ocorre a partir de poucas horas (4 h). São citados, ainda, edema de face, lesão de córnea, extubação acidental, perda de acesso vascular e taquicardia supraventricular [14][15][16][17] .…”
Section: Short-term Effects Of Prone Positioning On the Oxygenation Ounclassified